A performance study on a position control system using H[infinity] Loop shaping technique - Tay, Huck Sun. (2009)
This dissertation presents the design of a high-accuracy and high-speed position control system using an H8 Controller. The H8 Loop Shaped Controller will achieve an overall system robust stability while retaining the performance of a DC Motor precision positioning system. The analog and digital performance of this robust H8 Controller are studied and compared to an industrial PD Controller under the same specifications. Derivations and performance verifications for the controllers are obtained using the MATLAB and SIMULAB simulation softwares. The effects of the stability margin on the performance of the H8 Controllers are also discussed and presented.